ISLAMIC CONCEPTS OF EDUCATION IN THE CONTENT - Andi, Irfan; Muis, Abd.; Said, M.Said; Muis, Muis; Nur, Zulkifli (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research discusses the Islamic Concept of Education in the Womb. Why is this research interesting to discuss? Education during pregnancy is crucial in Islamic concepts, and Islam pays attention to the unborn child from an early stage. Therefore, the author explains how important it is to educate children in the future as an excellent investment to continue the sustainability of civilization as the nation's successors. To obtain an excellent investment in children, it is necessary to pay attention to the education and development of the child during pregnancy. Because the prenatal period is the foundation for further development (postnatal). Methodologically, this article is a literature review. Furthermore, this study is essentially a library research. The data analysis used in this research is content analysis, which involves analyzing the content of books. Another method used is the critical comparative method, which compares the thoughts of experts. From this research, it is found that among the verses about the education of children in the womb are found in Surah Ali-Imran verses 35 and 38, Surah Al-A’raf verse 172, As-Shaffat verse 100, and then Surah Al-Hajj verse 2. The development of the fetus in the womb begins with the creation of the human being in the initial phase, followed by the creation of the human being in the advanced phase, which goes through several stages: the stage of biological chemical elements from the essence of the earth, the stage of semen, the stage of sperm, the stage of clot, the stage of lump, the age of bones, the flesh period, and then the final creation period. Parents have the responsibility to educate and care for their children even during pregnancy.